2016
DOI: 10.1177/2047173416683425
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Children’s Rights Education: Three perspectives and three roles for teachers

Abstract: In this article, I argue that the world-view adopted by Children’s Rights Education advocates influences the form of education they present. In the first part of the article, I discuss three perspectives: (1) the legalistic perspective, which sees Children’s Rights Education as a matter of technical implementation; (2) the reformist-hermeneutic perspective, which focuses on the interpretation and elaboration of core children’s rights texts; and (3) the radical view, which sees Children’s Rights Education as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
0
16
0
4
Order By: Relevance
“…The second perspective is a hermeneutic perspective that examines texts related to children's rights. The third perspective is a radical perspective that examines the education of children's rights as an educational political struggle [23].…”
Section: Child Rights Educationmentioning
confidence: 99%
“…The second perspective is a hermeneutic perspective that examines texts related to children's rights. The third perspective is a radical perspective that examines the education of children's rights as an educational political struggle [23].…”
Section: Child Rights Educationmentioning
confidence: 99%
“…Previous research has identified the teacher as a key actor for the performance of children's human rights learning in school-both when it is successful and when it is less so (Jerome, 2016(Jerome, , 2018Leung et al, 2011;Waldron & Oberman, 2016;Zembylas et al, 2017). For example, Leung et al (2011) have studied the development and implementation of a school-based HRE curriculum in Hong Kong.…”
Section: Human Rights In Educationmentioning
confidence: 99%
“…Bu durum öğretmenlerin sahip oldukları yetersiz bilginin uygulama süreçlerini olumsuz yönde etkilemesi şeklinde açıklanmaktadır (Lo, Leung & Yuen 2015;Robson, 2016). Öğretmenlerin lisans eğitiminde almış oldukları derslerin çocuk haklarına ilişkin bakış açılarını etkilediği belirtilmektedir (Jerome, 2016;Leblebici & Çeliköz, 2017). Bu yüzden çocuk katılımına yönelik görüşlerin ve uygulamaların değişimi için bu süreçlerin hizmet öncesi eğitimden itibaren ele alınmasının gerekli olacağı düşünülmektedir.…”
Section: Tartışma Ve Sonuçunclassified